(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
We are concerned in the paper with spectral properties of indefinite Sturm – Liouville type problems with Cauchy boundary conditions where differential equations coefficients are real valued integrable functions, and the spectral parameter is also purely complex number. And also we get bounds on the real and imaginary parts of indefinite Sturm- Liouville problem with cauchy conditions.